2006
DOI: 10.1080/03056240601000945
|View full text |Cite
|
Sign up to set email alerts
|

Can the Poor Help GM Crops? Technology, representation & cotton in the Makhathini flats, South Africa

Abstract: The adoption of Genetically Modified (GM) cotton in South Africa's Makhathini Flats in 1998 was heralded as a case in which agricultural biotechnology could benefit smallholder farmers, and a model for the rest of the continent to follow. Using historical, political economic and ethnographic data, we find the initial enthusiasm around GM technology to be misguided. We argue that Makhathini's structured institutional framework privileges adopters of GM technologies through access to credit and markets. The adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 6 publications
0
34
0
2
Order By: Relevance
“…To minimise exclusion of relevant papers, test searches were performed using different combinations of search terms. A substantial amount of the existing research on the social impacts of GM crops focuses on the developing world in general, and on the rural poor in particular [13,16,27]. To cover all relevant social impact literature, it proved necessary to include the term "poverty" in the search, as a test search confirmed that this resulted in a significant number of relevant hits not captured otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…To minimise exclusion of relevant papers, test searches were performed using different combinations of search terms. A substantial amount of the existing research on the social impacts of GM crops focuses on the developing world in general, and on the rural poor in particular [13,16,27]. To cover all relevant social impact literature, it proved necessary to include the term "poverty" in the search, as a test search confirmed that this resulted in a significant number of relevant hits not captured otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Farmers on the irrigation scheme have enjoyed considerably more government support and resources than those on the drylands. 24,25 An estimated 2-3 women worked per farm, and approximately 4,400 women worked in agriculture on the Makhatini Flats. Before the survey, farmer unions and the community were informed about the study through workshops.…”
Section: Methodsmentioning
confidence: 99%
“…Smallholders, too, are poorly specified -one is led away from awkward class-filtered questions like asking whether the people displaced by 'land mobility' were not perhaps former and still aspiring smallholders. Indeed, as recent analysis of agricultural technology suggests (Witt et al 2006;Richards et al 2010) the category of 'the poor' itself seems to help the cause of agricultural technology, rather than the other way around (Glover 2010).…”
Section: Gendermentioning
confidence: 99%